Computational methods for algebraic spline surfaces : ESF exploratory workshop - Dokken, Tor; Jüttler, B. (Bert) (Springer, 2005)
"The papers included in this volume provide an overview about the state-of-the-art in approximative implicitization and various related topics, including both the theoretical basis and the existing computational techniques. The novel idea of approximate implicitization has strengthened the existing link between Computer Aided Geometric Design and classical algebraic geometry. There is a growing interest from researchers and professionals both in CAGD and algebraic geometry, to meet and combine knowledge and ideas, in order to better solve industrial-type challenges, as well as to initiate new directions for basic research. This volume will support this exchange of ideas between the various communities."--BOOK JACKET.